Adriatlas 3. Recherches pluridisplinaires récentes sur les amphores nord-adriatiques à l'époque romaine - Marion, Yolande; Tassaux, Francis; Machut, Pierre; Ben Amara, Ayed (PrimaLun@, 2020)
The study of ceramics needs to work more and more collaboratively together, between archaeologist, historians and archaeometrists : we are developing a real dialogue, which combine different disciplines in a broader perspective related to paleoenvironment as well as technics and economy. The Round Table from April 11th 2016, entitled "Recet multidisciplinary researches on north-adriatic amphoras in the Roman era" gathered some of the researchers from the four large centres of Padova, Vienna-Budapest, Aix-en-Provence and Bordeaux. All participants are involved in this multidisciplinary research with colleagues from Croatia who are widely committed to the archaeological and historic research of Istria. These researchers are motivated by the need to share their methods and reflections and to compare them in order to try finding answers to their problematic which are similar but in very different contexts.